THE ARTISTIC AND AESTHETIC CONCEPT OF CATHARSIS AND DEATH IN THE WORK OF MARK CHEREMSHYNA AND BOHDAN LEPKY - Vasylyshyn, Yaroslava (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
In this article, the author, applying comparative methods, explores the creative legacy of two Galician writers, Marko Cheremshyna and Bohdan Lepkyi. They, upholding the canon of Ukrainian modernism, depicted the rich world of Galicians in their literary works through striking symbolic images of “wings” and “time.” The novelty of the article lies in the author’s emphasis on how the writers revealed the mentality of their characters by portraying the liminality of their states: in catharsis, which occurred in moments of deep emotional elevation, and in death, which often enveloped young characters with its tragic “wings.” The author concludes that the elements of modern Ukrainian literature – pervni (from the beauty of words to the living truth of words to high spiritual qualities) grant us the right to identify our national identity within the European canon of modernism.